Ignatovia, a new replacement name for Lazarenkoa Ignatov & Ignatova (Leskeaceae, Bryophyta) - Deshmukh, Umakant Bhoopati (Phytotaxa, 2021)
A Bryophyte genus Lazarenkoa Ignatov & Ignatova (2019:227), family Leskeaceae Schimp.(1856:109) was described by Ignatov et al. (2019) on the basis of recent morphological and molecular results obtained by the plant species collected from region Primorsky Territory of Russia. Currently, genus Lazarenkoa Ignatov & Ignatova is monotypic having single species Lazarenkoa microphylla Ignatov & Ignatova (2019:227) and endemic to Russia. Unfortunately, this newly described Bryophyte genus Lazarenkoa Ignatov & Ignatova is a later homonym of Ukrainian Ascomycetes fungi genus Lazarenkoa Zerova (1938:170). Genus Lazarenkoa Zerova, is a monotypic with single species Lazarenkoa selaginellae Zerova (1938:170) belonging to the class Dothideomycetes Erikss. & Winka. (1997:5) described from shoot apices of Selaginella sibirica [Milde(1867:262)] Hieron(1900:290).